Colecistitis gangreno-gaseosa - Aliano, Artigas; Schneeberger, Federico; Ramírez, Wilson; Lorenzelli, Juan (Cirugía del Uruguay, 1980)
Three cases of emphisemato - gangrenous cholecystitis are related. A review of this pathology is done, its rare frequnecy, the predominance in males. The radiologic funding of air in the gallbladder and the vafue of cholecystectomy are pointed out.